2021
DOI: 10.1136/jech-2020-215608
|View full text |Cite
|
Sign up to set email alerts
|

Life course socioeconomic position and DNA methylation age acceleration in mid-life

Abstract: BackgroundAgeing biomarkers can help us better understand how well-established socioeconomic position (SEP) disparities in ageing occur. A promising new set of DNAm methylation (DNAm)-based ageing biomarkers indicate through their age acceleration (AA) measures if biological ageing is slower or faster than chronological ageing. Few studies have investigated the association between SEP and DNAm AA.MethodsWe used linear regression to examine the sex-adjusted relationships between childhood social class, adult so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
15
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 44 publications
6
15
2
Order By: Relevance
“…This study builds on a large body of past research examining the association between ACEs and mental and physical health, and a few studies linking ACEs to epigenetic age acceleration. Our findings are consistent with past findings that suggest second generation clocks are more consistently associated with ACEs in adults ( George et al, 2021 ), potentially because these clocks were trained to predict phenotypic indicators of accelerated aging and are more consistently associated with age-related health problems ( Horvath & Raj, 2018 ). This study also builds on this past body of research examining the association between ACEs and epigenetic clocks by utilizing a representative sample of US adults over the age of 50.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…This study builds on a large body of past research examining the association between ACEs and mental and physical health, and a few studies linking ACEs to epigenetic age acceleration. Our findings are consistent with past findings that suggest second generation clocks are more consistently associated with ACEs in adults ( George et al, 2021 ), potentially because these clocks were trained to predict phenotypic indicators of accelerated aging and are more consistently associated with age-related health problems ( Horvath & Raj, 2018 ). This study also builds on this past body of research examining the association between ACEs and epigenetic clocks by utilizing a representative sample of US adults over the age of 50.…”
Section: Discussionsupporting
confidence: 91%
“…Past research has reported both significant ( Colich et al, 2020 ; Jovanovic et al, 2017 ; Lawn et al, 2018 ; Marini et al, 2020 ) and null ( Austin et al, 2018 ; Fiorito et al, 2017 ; Simons et al, 2016 ; Verhoeven et al, 2018 ) results using the first generation clocks. Research using the second generation clocks has been more consistently supportive ( Belsky et al, 2020 ; George et al, 2021 ; Hamlat et al, 2021 ); however, prior research using the Health and Retirement Study suggests childhood adversity only accounts for a small proportion of PhenoAge ( Liu et al, 2019 ). Past investigations have been limited because they typically investigate only one epigenetic aging measure in a given analysis.…”
mentioning
confidence: 99%
“…This result is partially explained by our selection procedure in the training set, based on the time-to-CVD event. Also, it may support a previous report about DNAm as biomarkers of life course accumulation of exposure and stressors [52], leading to a better prediction of short-term outcomes rather than long-term risk. Thus, methylation levels are likely to have undergone severe changes as the follow-up time increased.…”
Section: Discussionsupporting
confidence: 83%
“…While decades of research demonstrate the long-term consequences of low childhood social position, recent studies suggest that the effects on epigenetic aging continue well into adulthood, but findings are mixed. Two separate studies found that low parental occupational status during childhood was associated with accelerated epigenetic aging in adulthood ( 6 , 47 ). These findings differ from those of a more recent study observing no association between parental occupational status during childhood and epigenetic aging in adulthood among participants in the Irish Longitudinal Study on Aging ( 85 ).…”
Section: Socioeconomic Position and Dna Methylationmentioning
confidence: 99%
“…Like early life SEP, low adult SEP is associated with differential DNAm levels at stress- and inflammation-related genes, including at the AVP gene (stress-related pathway) and the CD1D, F8, KLRG1, NLRP12, and TLR3 genes (inflammation-related pathways) ( 95 ). Furthermore, studies of SEP and epigenetic aging in adulthood demonstrate effects across epigenetic clocks, with low SEP attainment associated with accelerated DNAm aging across several epigenetic clocks, including Hannum’s clock,Levine’s PhenoAge,GrimAge,and (with weaker evidence of associations) Horvath’s clock ( 30 , 44 , 47 , 115 ).…”
Section: Socioeconomic Position and Dna Methylationmentioning
confidence: 99%